2023
DOI: 10.1155/2023/5141836
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Purine Metabolism-Related Genes PPAT and IMPDH1 in the Carcinogenesis of Intrahepatic Cholangiocarcinoma Based on Metabonomic and Bioinformatic Analyses

Abstract: In this study, we investigated the role of tumor microenvironment and serum differential metabolites in intrahepatic cholangiocarcinoma (ICC) carcinogenesis, providing new evidence for ICC treatment. Serum samples from healthy individuals and ICC patients were collected for metabolomic analysis. The purine metabolites such as inosine, guanosine, hypoxanthine, and xanthine were increased in patient serum. TCGA database samples were collected, and the correlation between purine metabolism-related genes and ICC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In addition, purine metabolism, which is inseparable from cell proliferation, was previously found to be enriched in several cancers ( Chen X-H. et al, 2019 ; Chen S. et al, 2022 ; Liu et al, 2023 ) and associated with poor efficacy of immunotherapy ( Li S. et al, 2022 ). Through pathway enrichment analysis and correlation detection using KEGG and Wiki databases, it was found that Piezo1 potentially facilitates the growth of breast cancer by modulating the purine metabolism of GUK1, POLD1 and APRT ( Chen and Chen, 2022 ).…”
Section: Association Of Piezo1 With Tumorsmentioning
confidence: 99%
“…In addition, purine metabolism, which is inseparable from cell proliferation, was previously found to be enriched in several cancers ( Chen X-H. et al, 2019 ; Chen S. et al, 2022 ; Liu et al, 2023 ) and associated with poor efficacy of immunotherapy ( Li S. et al, 2022 ). Through pathway enrichment analysis and correlation detection using KEGG and Wiki databases, it was found that Piezo1 potentially facilitates the growth of breast cancer by modulating the purine metabolism of GUK1, POLD1 and APRT ( Chen and Chen, 2022 ).…”
Section: Association Of Piezo1 With Tumorsmentioning
confidence: 99%